Economic feasibility analysis of a solar energy and solid oxide fuel cell-based cogeneration system in Malaysia - Akikur, R.K.; Saidur, R.; Ullah, K.R.; Hajimolana, S.A.; Ping, H.W.; Hussain, Mohd Azlan (Springer Verlag (Germany), 2016)
The current study presents a concept of a cogeneration system integrated with solar energy and solid oxide fuel cell technology to supply electrical and thermal energy in Malaysia. To appraise the performance, the system is analysed with two case studies considering three modes of operation. For the case-1, typical per day average electricity and hot water demand for a single family have been considered to be 10.3 kWh and 235 l, respectively. For the case 2, electricity and hot water demand are considered for the 100 family members. Energy cost, payback period, future economic feasibility and the environmental impact of the system are analysed for both cases using an analytical approach. The overall system along with individual component efficiency has been evaluated, and the maximum efficiency of the overall system is found to be 48.64 % at the fuel cell operation mode. In the present study, the proposed system shows 42.4 % cost effectiveness at higher load. Energy costs for case-1 and case-2 have been found to be approximately $0.158 and $0.091 kWh-1, respectively, at present. Energy costs are expected to be $0.112 and $0.045 kWh-1 for the case-1 and case-2, respectively, considering future (i.e. for the year 2020) component cost.